Pengembangan Materi Allah Hadir Dalam Alam Semesta (Kejadian 1:1-31) Berbasis Audio Visual Pada Pembelajaran Pendidikan Agama - Jessica Hutagalung; Lustani Samosir; Robinhot Sihombing (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The purpose of developing audio-visual media to produce and determine the feasibility of the material God is present in the audio-visual-based universe developed in the subject of Christian Religious Education and Ethics grade III Elementary School. The research is a research and development (research and development) of audio-visual media that aims to produce products and test the effectiveness of products. The research took place in a public elementary school in Sipoholon District, North Tapanuli Regency. The research was conducted from August to September 2023. Research and development was conducted using the ADDIE model proposed by Dick and Carry.